Intelligent tutoring system web package / Rakesh Jaya Prakasam - Rakesh Jaya , Prakasam (2001)
Education learning package has been in the market and in the web for a long time. Most of the web pages however are specific for primary school student children and kids and for other computer learning. For the example, "Ujian Penilaian Sekolah Rendah" (UPSR) for Bahasa Melayu subject is one of the learning web pages for the primary school student. None of the learning package or web page available in the software market is developed for the Physics subject in the SPM examination. Furthermore, most of the learning web page do not have an attractive user interface and do not provide any important elements regarding on examination like SPM. Intelligent Tutoring System( ITS), for SPM Physics is thus proposed to overcome these shortcomings. ITS is an Internet-based learning system. This system has covers four main syllabus or topics out of seven topics of SPM Physics paper. The system provides short notes, tutorial part, experiments part and a modal exam paper to prepare the student for the SPM Physics examination. Compare to other learning web page, ITS provides an attractive user interface element that includes images (in graphics or animation way), this making the learning of the way are more efficient method for this subject. And also, experiment applications are also provided to let students conduct the Physics experiments by monitoring them how to conduct the experiment with voice capability. This is one of the system intelligent specifications. This voice would construct the student to perform the experiment steps correctly. For each topic, the system provided a tutoring module for user or student has comprehended them regarding on those topic. After they finished every topic, the student will enter into exam module where they will sit this exam similar to their SPM exam. Final result will be displayed after they complete answering the entire exam question. This is briefly about this learning system. In order to develop a comprehensive system, related information is gathered from books, Internet surfing and other learning materials. After conducting a thorough analysis, the SDLC (System Development Life Cycle) strategy or methodology was selected to develop this project. Internet is chosen to be the platform for the development of this project because the user or student can easily access this system any time and very easy and also freely available. Macromedia Authorware Attain 5 is selected as the main system development tools and also other programming tools like Java Script and HTML will be added to develop this system. It is hope that the development of ITS will assist the upper level secondary school students to achieve a better result in the SPM examination especially on Physics subject.